2019
DOI: 10.1371/journal.pone.0218746
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal growth velocity of preterm infants: The weight Z-score change versus Patel exponential model

Abstract: Background Different methods are used to assess the growth of preterm infants during neonatal hospital stay. The primary objective was to compare two methods for assessing growth velocity: g/kg/d according to the Patel exponential model (EM) and change in weight z-score (ZS) according to Fenton curves. The secondary objective was to highlight factors influencing the level of agreement between the two methods. Methods Preterm infants born before 33 weeks were included. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Generalized estimating equation (GEE) models were used to analyze trajectory trends of these growth measurements over time. Growth velocity was defined as the change of z-score over the periods [ 15 , 16 ] using the lincom function of GEE models. Gestational age, gender, birth weight z-score, and intrauterine growth status was adjusted as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Generalized estimating equation (GEE) models were used to analyze trajectory trends of these growth measurements over time. Growth velocity was defined as the change of z-score over the periods [ 15 , 16 ] using the lincom function of GEE models. Gestational age, gender, birth weight z-score, and intrauterine growth status was adjusted as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…We used two EUGR indicators based on changes in weight between birth and discharge from the neonatal hospitalisation which are most commonly used in the scientific literature. [15][16][17][18] The first indicator was birthweight and discharge-weight Zscore differences using Fenton's postnatal growth charts (Fenton delta Z-score). 10 The second indicator uses an exponential model of growth velocity to measure the average gain in grams per kilogram (kg) of weight per day based on birthweight, discharge weight and number of days of hospitalization (Patel's weight-gain velocity).…”
Section: Measures Of Postnatal Extrauterine Growth Restrictionmentioning
confidence: 99%
“…Our analysis of the overlap between the groups found that risks were highest when boys were classified as severely EUGR by both measures and also moderately elevated when they were severely EUGR by Fenton. Fenton's delta Z-score has been considered by some researchers to be preferable because it adjusts for GA and sex, 17,46 whereas Patel's weight-gain velocity is calculated in the same manner for all neonates. 8 We do not know of any studies that have investigated the effect of combining information from both indicators.…”
Section: Choice Of the Weight Gain Velocity Indicatormentioning
confidence: 99%
“…Generalized estimating equation (GEE) models were used to analyze trajectory trends of these growth measurements over time. Growth velocity was de ned as the change of z-score over the periods (15,16) using the lincom function of GEE models. Gestational age, gender, birth weight zscore, and intrauterine growth status was adjusted as covariates.…”
Section: Statistical Analysesmentioning
confidence: 99%